Upaya Meningkatkan Keterampilan Menulis Naskah Drama dengan Menggunakan Media Boneka (Stick Wayang Orang) - Yulianti, Etik (Nur Science Institute, 2021)
This study aims to improve the skills of writing drama scripts through the use of puppet media (wayang orang stick) in class VIII E SMP Negeri 11 Surakarta semester 1 of the 2013/2014 academic year. This classroom action research was conducted at SMPN 11 Surakarta in the first semester of the 2013/2014 academic year for 6 months. The research subjects were 32 students of class VIIIB SMPN 11 Surakarta. The method used in this research is a classroom action research method which is carried out in 3 cycles through 4 stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. In the implementation of classroom action research using observation sheets. Data analysis used comparative descriptive analysis technique. The results showed that the use of puppet media (wayang orang stick) can improve the skills of writing drama scripts in class VIII E students of SMP Negeri 11 Surakarta in semester 1 of the 2013/2014 academic year.